Some experiences in using virtual machines for teaching computer networks - Nabhen, Ricardo (2006)
Laboratory practice is a fundamental aspect of computer network learning. Experiments tend to be very specific, frequently demanding changes in the local network topology and privileged access to the operating system configuration. These features impose a specific and exclusive laboratory for network teaching experiments. However, it is not always possible to provide such laboratory; the reality in most institutions is to have shared laboratories, used by different students and disciplines. This problem can be alleviated by the use of virtual machines, allowing each student to build his/her own network experiment, using the appropriate topology, and thus not disturbing the other activities running in the lab. This paper presents some experiences in using virtual machines to teach advanced aspects of computer networks, such as IPSec, firewalls and network services. Also, some key points are highlighted in order to show the benefits of virtual machines for pedagogical practice.